Endophytes From Algae, a Potential Source for New Biologically Active Metabolites for Disease Management in Aquaculture - Deutsch, Ynon; Gur, Lior; Berman Frank, Ilana; Ezra, David (Frontiers in Marine Science, 2021)
Endophytes are microorganisms that live inside the plant tissue without causing external symptoms. All plants in nature harbor endophytes. Some endophytes produce and secrete biologically active compounds, known as secondary metabolites, which can help the host plant cope with bacterial, fungal and other pest pathogens. Endophytes are isolated from aquatic plants and algae. Diseases are detrimental in the aquaculture industry where chemical pesticides and antibiotics are widely used in an attempt to cope with fish pathogens. However, the ability to prevent disease outbreaks in aquaculture is currently extremely limited. Here, we isolated 173 bacterial and fungal endophytes from 16 Mediterranean seaweed and 4 algae from fresh or thermo-mineral water. We found 88 endophytes (51%) with biological activity against four common aquaculture pathogens. Fifty endophytes (29%) caused mortality of at least one of these four pathogens. We identified 23 ¬¬bioactive endophytes, 18 of which are from the Bacilli class. Our findings suggest that macroalgae from different aquatic environments can serve as a good source of potential biocontrol agents against aquaculture diseases. To the best of our knowledge, there are no published studies demonstrating the use of algal endophytes to control aquaculture diseases. Our study may lead to finding new molecules for use as novel environmentally friendly products that will solve one of the most challenging problems for the growing aquaculture industry: pathogens and pests.